2017
DOI: 10.24925/turjaf.v5i8.898-907.1224
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Zinc Application Methods on Yield and Grain Zinc Concentration of Bread Wheat Varieties

Abstract: This study was carried out to elucidate the impacts of zinc (Zn) treatments on growth, development, quality and yield of commonly sown bread wheat cultivars under field conditions of Çukurova Region. Three different bread wheat cultivars (Adana-99, Ceyhan-99 and Pandas) were experimented in randomized complete blocks-split plots experimental design with 3 replications. Field experiments were performed by two different Zn application methods; via soil and via soil+foliage. In the both trials, 0, 5, 10, 20, 30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The reason for the variation of the varieties and their superiority in the proportion of protein may be attributed to the specific weight. [54] indicated that the varieties with higher protein content have a relatively lower specific weight than the varieties with lower protein content [55] Relatively table (5). indicated that there is a discrepancy in the efficiency of the vegetative system of different cultivars in redistributing the synthesize protein within the plant, which causes a discrepancy in the proportion of grain protein between Different cultivars, and it was also found that the cultivars differ in the efficiency of their roots in absorbing nitrogen from the soil and their ability to reduce nitrates during the period of grain filling, and these results are in line with previous studies [56][57][58][59].…”
Section: Protein Percentage (%)mentioning
confidence: 99%
“…The reason for the variation of the varieties and their superiority in the proportion of protein may be attributed to the specific weight. [54] indicated that the varieties with higher protein content have a relatively lower specific weight than the varieties with lower protein content [55] Relatively table (5). indicated that there is a discrepancy in the efficiency of the vegetative system of different cultivars in redistributing the synthesize protein within the plant, which causes a discrepancy in the proportion of grain protein between Different cultivars, and it was also found that the cultivars differ in the efficiency of their roots in absorbing nitrogen from the soil and their ability to reduce nitrates during the period of grain filling, and these results are in line with previous studies [56][57][58][59].…”
Section: Protein Percentage (%)mentioning
confidence: 99%
“…However, generally warm and drought climatic conditions create the ideal environment for salinity and barrenness formation in any region where the wheat grows (Başer et al, 2005). On the other hand, the accumulation of zinc, iron, lead, cadmium, nickel and other heavy metals in dense industrial zones which are close to cultivation lands affect wheat crop production by leading to heavy metal toxicity ( Mutlu et.al., 2013;Mutlu et.al., 2014;Mutlu et.al., 2016;Mutlu and Kurnaz, 2017;Barut et al, 2017;Kurnaz and Turfan, 2017;Sarıyıldız et al, 2017;Mutlu and Kurnaz, 2018). Many authors stated that salinity, heavy metals and element toxicity, excessive calcerous soil and also drought especially before grain filling may reduce leaf and stem properties such as leaf area, length of leaf, length and strength of internode (Ostrowska et al, 2014;Turkyılmaz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%